Simulating with RICE coalitionally stable burden sharing agreements for the climate change problem - Johan Eyckmans; Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 1999)
In this paper we test empirically with the Nordhaus and Yang (1996) RICE model the core property of the transfer scheme advocated by Germain, Toint and Tulkens (1997). This scheme is designed to sustain full co-operation in a voluntary international environmental agreement by making all countries at least as well off as they would be by joining coalitions adopting emission abatement policies that maximise their coalition payoff; under the scheme no individual country, nor any subset of countries would have an interest in leaving the international environmental agreement. The simulations show that the transfer scheme yields an allocation in the core of the carbon emission abatement game associated with the RICE model. Finally, we discuss some practical implications of the transfer scheme for current climate negotiations.
Keywords: 330; Environmental economics; Climate change; Burden sharing; Simulations; Core of co-operative games; Internationale Umweltpolitik; Klimaschutz; Umweltökonomik; Klimawandel; Theorie